Differences in Kinematic and Muscle Activity Associated with ACL Injury Risk in Second Division Female Football Players: Influence of Direction Task. - Ferrández Laliena, Loreto; Vicente-Pina, Lucía; Sánchez-Rodríguez, Rocío; Chapman, Graham; Jimenez Heredia, Jose; Hidalgo García, César; Tricás Moreno, José Miguel; Lucha López, María Orosia (Jornada de Jóvenes Investigadores del I3A, 2025)
This study aims to analyze key knee kinematic variables and lower-limb muscle activity to identify differences in motor control and movement quality related to the anterior cruciate ligament (ACL) injury mechanism. The findings may identificate at-risk players and improve prevention strategies by assessing functional movement patterns during dynamic tasks.